Peran Bank Sampah Sebagai Salah Satu Bentuk Strategi Pengelolaan Sampah Dalam Meningkatkan Kesejahteraan Warga Dusun Duren Gede - Cahyani, Regita Tri; Fitriani, Ika Lutfia; Zahra, Hana (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2024)
Waste management poses a serious challenge in maintaining environmental cleanliness and health. One solution that can be implemented is through the Waste Bank approach. This research aims to illustrate the role of the Waste Bank as a waste management strategy in improving the welfare of Duren Gede Village residents. The research method used is a survey and interviews with Waste Bank members and the surrounding community. The results show that the Waste Bank in Duren Gede Village acts as a center for the collection, processing, and utilization of waste. Through active participation of residents in the Waste Bank, the amount of waste generated can be managed more efficiently. In addition, environmental education programs implemented by the Waste Bank also provide understanding to the community about the importance of waste management.With the existence of the Waste Bank, there is an increase in income for residents through the incentive system applied. The utilization of waste as a local economic resource also contributes positively to the economic development and welfare of the Duren Gede Village community.